Validación de un rompecabezas como recurso lúdico digital en salud bucal para niños/niñas entre 7 y 10 años de edad (2021)
At present, the teaching of correct oral hygiene care in the child population has become a challenge, because the methods that were used have become outdated as the years go by, it is known that the beginning of a good care of the oral cavity and a good development in oral hygiene is given from a premature teaching of it. The importance of having a validated instrument or material is emphasized, because allows the effectiveness of its use, the validation process strengthens and increases reliability at the time of development and thus allows the tool to be modified or adapted for a specific intervention